Integration of Emerging Technologies in Teacher Education for Global Competitiveness - Ibrahim, Umar (International Journal of Educational and Life Sciences, 2024)
This paper explores the critical theme of integrating emerging technologies into teacher education to enhance global competitiveness. In the dynamic landscape of education, the demand for innovative teaching approaches has never been more pronounced. This paper provides a comprehensive review of current literature, presenting a theoretical framework that underpins the integration of emerging technologies in teacher education. Methodologies employed in relevant studies are discussed, and a collection of case studies and examples illustrate successful implementations of technology in teacher education programs across diverse global contexts. Challenges associated with the integration of emerging technologies are examined, and practical solutions are proposed. The impact of these technological innovations on global competitiveness in education is analyzed, emphasizing their contribution to the development of essential 21st-century skills. The role of ongoing professional development for educators in effectively incorporating emerging technologies into their teaching practices is explored, along with insights into effective training programs and resources. The paper concludes with a forward-looking discussion on potential future trends and developments in the integration of emerging technologies in teacher education. The importance of continued research and innovation in shaping the future of education on a global scale is emphasized. Through this exploration, the paper seeks to contribute valuable insights to the field and encourage further inquiry into the transformative potential of emerging technologies in teacher education.